2000
DOI: 10.1111/j.1745-6606.2000.tb00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes of Singaporeans towards Genetically Modified Food

Abstract: This study examines the perceptions and attitudes of Singaporean residents who attended the first public lecture on genetically modified (GM) food in the country. Scales were developed for the underlying consumer concerns, and their relationship with one another and with demographic variables were examined. Slightly more than half of those who attended the talk (n= 417) indicated that they were worried about GM foods and 86 percent agreed or strongly agreed that GM foods should be labeled. Issues relating to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 5 publications
4
35
1
4
Order By: Relevance
“…The study revealed that women considered the risks of current GM technology to be greater than men considered them to be (average value of risks under scenario one was 4 as opposed to 3.5) (Table 3). This finding corresponds to surveys conducted with members of the general public that women considered GM food to be more risky than men (Subrahmanyan and Cheng, 2000;Moon and Balasubramanian, 2001). A study by Isaacs (2001) investigating acceptance of GM foods found no significant difference in willingness to buy or unwillingness to buy among many socio-demographic variables.…”
Section: Article In Presssupporting
confidence: 82%
See 1 more Smart Citation
“…The study revealed that women considered the risks of current GM technology to be greater than men considered them to be (average value of risks under scenario one was 4 as opposed to 3.5) (Table 3). This finding corresponds to surveys conducted with members of the general public that women considered GM food to be more risky than men (Subrahmanyan and Cheng, 2000;Moon and Balasubramanian, 2001). A study by Isaacs (2001) investigating acceptance of GM foods found no significant difference in willingness to buy or unwillingness to buy among many socio-demographic variables.…”
Section: Article In Presssupporting
confidence: 82%
“…Previous studies have revealed a diversity of consumer concerns relating to GM food, including unpredictable health risks (Lemkow, 1993;Olubobokun et al, 2001;Isaacs, 2001;Subrahmanyan and Cheng, 2000;Verdurme et al, 2001a), environmental safety risks (Olubobokun et al, 2001;Isaacs, 2001), and the structure of agri-business (Isaacs, 2001). There are fears that there may be long-term environmental effects (Lemkow, 1993), risks to future generations (Poortinga and Pidgeon, 2003;Rosati and Saba, 2000), and long-term food safety issues (Grove-White et al, 1997).…”
Section: Gm Technology and Consumer Concernsmentioning
confidence: 97%
“…Negative opinions of GM foods have also been reported from other countries including Singapore (Subrahmanyan and Cheng, 2000) and New Zealand (Campbell et al, 2000;Gamble and Gunson, 2002). Consumer concerns regarding GM foods have been categorised as: concern for public safety, moral concerns, and fear of loss of individual life (Bredahl et al, 1998).…”
Section: Consumer Attitudesmentioning
confidence: 77%
“…Kajian sikap terhadap GMF daripada konteks pengguna Asia turut melibatkan negara-negara maju seperti Jepun (Ishiyama et al 2012), Korea Selatan (Kim, Kim & Besley 2012), Taiwan (Chen 2008(Chen , 2011 dan Singapura (Subrahmanyan & Cheng 2000). Dapatan ini menunjukkan pembangunan model sikap pengguna terhadap GMF masih kurang dijalankan daripada perspektif pengguna di negara-negara sedang membangun.…”
Section: Pengenalanunclassified